Transitional Justice in Aparadigmatic Contexts: Accountability, Recognition, and Disruption - Destrooper, Tine (Taylor & Francis Group, 2023)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of Tables and Figures -- Acknowledgements -- Author Biographies -- Abbreviations and Acronyms -- Introduction: Transitional Justice in Aparadigmatic Contexts -- Chapter 1 Diasporic and Domestic: Leveraging Criminal Accountability for Transitional Justice in the Middle East -- Chapter 2 Overcoming the Justice Impasse in Syria -- Chapter 3 Imagining Transitional Justice in Turkey's Ongoing Kurdish Conflict -- Chapter 4 Transitional Justice in Afghanistan: A Hegemonic Power Discourse -- Chapter 5 Unable to See the Forest for the Trees: Transitional Justice and the United States of America -- Chapter 6 Transitional Justice in the North Atlantic: The Greenland Reconciliation Commission and the Role of Political Authority -- Chapter 7 Transitional Justice and the British Military in Iraq -- Chapter 8 Divergent Ambitions: Bracketing the Disruptive Potential of Transitional Justice in Belgium -- Chapter 9 Transitional Justice for European Terror Actors: Disrupting Europe's Security/Rights Terror Law Impasse -- Chapter 10 Addressing the Legacies of the Past: Historical Commissions in Consolidated Democracies -- Chapter 11 Theorising Transitional Justice in Ongoing Conflict -- Concluding Remarks -- Index.